The Effect Pharmacy Counseling Satisfaction and Compliance Taking Medication Type 2 DM Patients with Hypertension Complications Tebet Hospital - Rizkiah Kiah; Priyanto Priyanto; Dwitiyanti Dwitiyanti (Poltekkes Kemenkes Jakarta III, 2026)
Pharmacist counseling is intervention that can increase patient satisfaction and compliance with treatment. This study aims to analyze the effect of pharmacist counseling on the level of patient satisfaction and adherence to taking medication in patients with type 2 diabetes mellitus complicated by hypertension. This research uses a one group pretest-posttest design. The research subjects were 95 patients who met the inclusion criteria and were taken using the MMAS-8 method and the satisfaction method. Satisfaction and compliance measurements were carried out before and after pharmacist counseling. Data analysis was carried out descriptively, Wilcoxon signed-rank test with a significance level of 5%. The results of the analysis showed that the average patient satisfaction score increased from 0.40 before counseling to 0.76 after counseling, with a difference of 0.36. The Wilcoxon test showed p = 0.00 (p < 0.05), which indicates there is a significant difference in the level of patient satisfaction. In the medication adherence variable, the average score increased from 27.94 to 51.27 with a difference of 23.34. The Wilcoxon test results obtained p = 0.00 (p < 0.005), which shows that there is a significant difference in the level of adherence to taking medication before and after counseling. Analysis based on the compliance category after counseling experienced an increase marked by the dominance of the high compliance category with an average of 51.27. Analysis based on satisfaction categories after counseling experienced an increase marked by the dominance of the high satisfaction category with an average of 6.07.